STUDI EX POS FACTO PENGARUH PENGALAMAN SAINTIFIK DAN PENGETAHUAN LINGKUNGAN TERHADAP KEPEDULIAN LINGKUNGAN MAHASISWA PENDIDIKAN BIOLOGI TAHUN AKADEMIK 2015/2016 - Agus Sujarwanta; Rasuane Noor; Widya Sartika Sulistiani (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2017)
In the environment of campus Muhammadiyah University of Metro, students care in maintaining the cleanliness of the campus can be said to be lacking. Many objects are thrown away at random, such as: candy wrappers, plastic snack foods, and various papers in the campus environment. This objectives of the research to obtain an empirical of the influence of scientific experience and environmental knowledge on environmental awareness.The research method used is ex post facto. The research was conducted in the Biology Education Department, Faculty of Teacher Training and Education, Muhammadiyah University of Metro. Implementation of research from March to July 2016. The population of this study is the students of Biology Education Departmen who take the course of Environmental Knowledge in the even semester of Academic Year 2015/2016 amounted to 124 people. Research sample is taken with proportional random sampling as much 68 people. Data analysis techniques using Two-Way Variance Analysis.Conclusion of the research are follow: 1. There is influence of scientific experience to environmental awareness, 2. There is influence of environmental knowledge to environmental awareness, and 3. There is no influence of scientific experience and environmental knowledge to environmental awareness.